2010
DOI: 10.1021/ef900886e
|View full text |Cite
|
Sign up to set email alerts
|

Bitumen Characterization and Pseudocomponents Determination for Equation of State Modeling

Abstract: The phase behavior and thermodynamic properties of heavy oil and bitumen are of crucial importance for their in situ recovery, pipeline transportation, and upgrading; however, bitumen is a complex mixture of organic compounds whose chemical structures are not well understood. Therefore, bitumen is commonly characterized as a mixture of pseudocomponents derived from experimental data. This manuscript is intended to characterize and define the thermodynamic properties of Alberta bitumens. It has been undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 11 publications
3
35
0
Order By: Relevance
“…Experimental data in the vapour-liquid-liquid (VLL) region cannot be represented accurately by the proposed model. However, this inaccuracy has also been reported for other predictive models, such as those of Kariznovi et al [3] and Mehrotra and Svrcek. [2] Experimental solubility data of CO 2 in Cold Lake bitumen for temperatures up to 523.15 K and pressures up to 16 MPa have been reported by Yu et al [14] Experimental solubility data of CO 2 in Peace River bitumen for temperatures up to 473.15 K and pressures up to 10 MPa have been reported by Mehrotra et al [18] Our proposed model showed good accuracy in representing the experimental solubility data of gaseous and super critical CO 2 in bitumen, as illustrated in Figures 5 and 6.…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…Experimental data in the vapour-liquid-liquid (VLL) region cannot be represented accurately by the proposed model. However, this inaccuracy has also been reported for other predictive models, such as those of Kariznovi et al [3] and Mehrotra and Svrcek. [2] Experimental solubility data of CO 2 in Cold Lake bitumen for temperatures up to 523.15 K and pressures up to 16 MPa have been reported by Yu et al [14] Experimental solubility data of CO 2 in Peace River bitumen for temperatures up to 473.15 K and pressures up to 10 MPa have been reported by Mehrotra et al [18] Our proposed model showed good accuracy in representing the experimental solubility data of gaseous and super critical CO 2 in bitumen, as illustrated in Figures 5 and 6.…”
Section: Resultsmentioning
confidence: 56%
“…Therefore, we use the same terminology throughout this article. Letting subscript s and superscript b refer to the solvent and bitumen, respectively, we can write the equality of fugacity for the dissolved gases in the gas and bitumen phase at equilibrium condition as: Mehrotra and Svrcek [19] Proposed model 1.79 287.85-371.35 2.14-10.95 Kariznovi et al [3] 8.89 Eastick et al [5] 6.8 A 3152.545 Mehrotra and Svrcek [2] 1.9 Yu et al [14] Proposed Huang and Radosz [9] 5.675 Huang and Radosz [8] 5.44…”
Section: Thermodynamic Modelmentioning
confidence: 99%
See 3 more Smart Citations